Experimental study of a vibration based energy harvesting system for an RFID module - Khemmanee, B.; Tattiwong, K.; Bunlaksananusorn, C. (My University, 2018)
In recent years, an application of a piezoelectric transducer to harvest energy from ambient vibrations has been a subject of intense research. As the material technology advances, the amount of energy being able to produce by the transducer continues to increase. This paper presents an experimental study of a vibration based energy harvesting system for an RFID module. The system consists of a piezoelectric transducer, a power management circuit based on a buck converter, and an RFID module. The transducer converts mechanical movement produced by a finger press into a voltage to charge an input capacitor. The buck converter then converts the input capacitor voltage into a stable DC output voltage to power the RFID module. Experimental results are presented to validate the performance of the proposed energy harvesting system.
Keywords: Piezoelectric transducer; Power management circuit; RFID